2019
DOI: 10.1002/bin.1663
|View full text |Cite
|
Sign up to set email alerts
|

Diaphragmatic breathing as treatment for escape‐maintained aggression

Abstract: Coping skills, such as diaphragmatic breathing, are commonly recommended to help individuals work through challenging situations. We evaluated diaphragmatic breathing as treatment for aggression of three individuals diagnosed with autism spectrum disorder or Angelman syndrome. Functional analysis results demonstrated that each participant engaged in aggression maintained by social-negative reinforcement. Diaphragmatic breathing treatment without extinction was conducted in a work context and involved prompting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 27 publications
0
0
0
Order By: Relevance
“…To illustrate, interventions based on heart rate (variability) biofeedback can decrease anger in adolescents and improve emotion-regulation in offenders, which is an often-re-occurring treatment goal for forensic psychiatric patients (Savard, 2017;Gray et al, 2019). Moreover, diaphragmatic breathing has shown to be supportive in reducing aggressive behavior in various psychiatric patient groups, by modulating the heart rate and specific neural circuits that are involved in emotion regulation (Gillespie et al, 2012;Phillips et al, 2019). Regarding the effectiveness of DEEP: recent studies have also shown DEEP to be effective in reducing stress and anxiety in students and in showing less disruptive behavior in adolescents with behavioral problems (Van Rooij et al, 2016;Bossenbroek et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…To illustrate, interventions based on heart rate (variability) biofeedback can decrease anger in adolescents and improve emotion-regulation in offenders, which is an often-re-occurring treatment goal for forensic psychiatric patients (Savard, 2017;Gray et al, 2019). Moreover, diaphragmatic breathing has shown to be supportive in reducing aggressive behavior in various psychiatric patient groups, by modulating the heart rate and specific neural circuits that are involved in emotion regulation (Gillespie et al, 2012;Phillips et al, 2019). Regarding the effectiveness of DEEP: recent studies have also shown DEEP to be effective in reducing stress and anxiety in students and in showing less disruptive behavior in adolescents with behavioral problems (Van Rooij et al, 2016;Bossenbroek et al, 2020).…”
Section: Introductionmentioning
confidence: 99%